2016
DOI: 10.1377/hlthaff.2016.0848
|View full text |Cite
|
Sign up to set email alerts
|

Preventable Death Rates Fell Where Communities Expanded Population Health Activities Through Multisector Networks

Abstract: The US health system faces mounting pressure to improve population health. Research suggests a need for greater coordination and alignment across the sectors that deliver medical, public health, and social services. This study uses sixteen years of data from a large cohort of US communities to measure the extent and nature of multisector contributions to population health activities and how these contributions affect community mortality rates. The results show that deaths due to cardiovascular disease, diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
108
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 29 publications
1
108
0
3
Order By: Relevance
“…Local governing boards of health are hypothesized to generate enhanced public and political support for allocating resources to public health, because their membership frequently includes individuals who have political access, professional credibility, and/or technical expertise that can be used to attract and maintain resources. Several prior studies have found evidence of higher levels of spending and performance among local public health agencies that are governed by local boards of health (Mays and Smith ; Mays, Mamaril, and Timsina ). Conversely, spending is expected to be lower among public health agencies that operate under the centralized control of state government.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Local governing boards of health are hypothesized to generate enhanced public and political support for allocating resources to public health, because their membership frequently includes individuals who have political access, professional credibility, and/or technical expertise that can be used to attract and maintain resources. Several prior studies have found evidence of higher levels of spending and performance among local public health agencies that are governed by local boards of health (Mays and Smith ; Mays, Mamaril, and Timsina ). Conversely, spending is expected to be lower among public health agencies that operate under the centralized control of state government.…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of research indicates that local variation in public health resources contributes to differences in health outcomes observed across communities (Grembowski et al 2010;Mays and Smith 2011;Brown 2014Brown , 2016Mays, Mamaril, and Timsina 2016). These findings raise the possibility that expanded financing for public health activities could lower overall disease burden and thereby constrain medical spending.…”
mentioning
confidence: 99%
“…Their efforts are showing promise, including improvements in health outcomes and reductions in mortality. 19,20 For patients with COPD, this would mean not only that their community's health care system can link them to support services for their social needs, but also that they can live in smoke-free housing.…”
Section: Corresponding Authormentioning
confidence: 99%
“…A 2013 nationwide survey found that 84% of state public health practitioners engaged in collaboration activities but that these activities were primarily client-oriented and focused on secondary rather than primary prevention (7). A 2016 study found that in communities that implemented population health activities involving multisector partners, resident death rates from cardiovascular disease, diabetes, and influenza were reduced (8). A recent report concluded that these partnerships are critical components of a comprehensive community wellness approach that will ensure seamless care and prevention for everyone (9).…”
Section: Introductionmentioning
confidence: 99%